2015
DOI: 10.1007/s10856-015-5605-1
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz contact resonance spectroscopy for nanoscale characterisation of structural and mechanical properties of biological, dental and pharmaceutical materials

Abstract: Scanning probe microscopy has been widely used to obtain topographical information and to quantify nanostructural properties of different materials. Qualitative and quantitative imaging is of particular interest to study material-material interactions and map surface properties on a nanoscale (i.e. stiffness and viscoelastic properties). These data are essential for the development of new biomedical materials. Currently, there are limited options to map viscoelastic properties of materials at nanoscale and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Other AFM-based methods used to quantitatively map dissipative forces may also be suitable for incorporation. 23,24 Development of corrective approaches and further understanding of relationships between thermomechanical properties, probesample interactions, and AFM-IR signal transduction will likely require further experimental work with well-defined model structures. Lahiri et al, have previously reported rigorous experimental evaluation of AFM-IR response to nanopatterned poly(methyl methacrylate) structures prepared by electron beam lithography.…”
Section: Resultsmentioning
confidence: 99%
“…Other AFM-based methods used to quantitatively map dissipative forces may also be suitable for incorporation. 23,24 Development of corrective approaches and further understanding of relationships between thermomechanical properties, probesample interactions, and AFM-IR signal transduction will likely require further experimental work with well-defined model structures. Lahiri et al, have previously reported rigorous experimental evaluation of AFM-IR response to nanopatterned poly(methyl methacrylate) structures prepared by electron beam lithography.…”
Section: Resultsmentioning
confidence: 99%
“…Semi-thin sections were transferred to zinc selenide prisms (Anasys instruments) and scanned on SPM (AFM NanoIR, Anasys instruments) in LCR mode to evaluate morphology in 3D and the variations in nanomechanical properties across the section [37]. To obtain the nanomechanical spectra, images were taken in LCR mode over a drive frequency range of 1-1000 kHz at an increment rate of 100 kHz.s -1 with following parameters: scan rate of 0.30 Hz, resolution 500 × 200 points and drive strength of 15%.…”
Section: Particle Uptake Studiesmentioning
confidence: 99%
“…In terms of mechanical properties characterization, conventional approaches such as acoustic impedance, spherical indentation, and nanoindentation are also suitable only for larger particles and simply cannot determine the nanomechanical domain with a resolution <20 nm . To address these limitations, a number of advanced AFM modes have been developed such as the amplitude modulation–frequency modulation atomic force microscopy, force modulation, friction force microscopy, and contact resonance microscopic techniques such as piezoresponse microscopy and atomic force acoustic microscopy .…”
mentioning
confidence: 99%
“…A promising new approach for mapping nanomechanical properties is the use of Lorentz contact resonance (LCR) spectroscopy. In LCR, the actuation of the cantilever is achieved with an oscillating Lorentzian force ( Figure b) and it is not sample specific . The sample is characterized based on the force modulation and the detection of changes to the cantilever deflection (frequency and amplitude), which directly correlate with viscous and elastic properties .…”
mentioning
confidence: 99%
See 1 more Smart Citation